2004
DOI: 10.1086/425001
|View full text |Cite
|
Sign up to set email alerts
|

An Open, Randomized, Controlled Trial of Penicillin, Doxycycline, and Cefotaxime for Patients with Severe Leptospirosis

Abstract: Doxycycline or cefotaxime is a satisfactory alternative to penicillin G for the treatment of severe leptospirosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
1
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(113 citation statements)
references
References 24 publications
4
99
1
5
Order By: Relevance
“…28 However, in several studies reporting serologic surveys in local populations in Southeast Asia, serogroup Icterohaemorrhagiae was not shown to be the dominant serogroup. [29][30][31][32] Leptospirosis was seen as multi-organ failure and a potentially life-threatening disease in many of our patients. This type of manifestation was significantly more common in patients presumptively infected with serogroup Icterohaemorrhagiae.…”
Section: Discussionmentioning
confidence: 87%
“…28 However, in several studies reporting serologic surveys in local populations in Southeast Asia, serogroup Icterohaemorrhagiae was not shown to be the dominant serogroup. [29][30][31][32] Leptospirosis was seen as multi-organ failure and a potentially life-threatening disease in many of our patients. This type of manifestation was significantly more common in patients presumptively infected with serogroup Icterohaemorrhagiae.…”
Section: Discussionmentioning
confidence: 87%
“…These samples were collected as part of studies investigating the causes of fever. 4,7 This clinical study was approved by the Ethical Review Subcommittee of the Public Health Ministry of Thailand, and Siriraj Institutional Review Board Faculty of Medicine Siriraj Hospital, Mahidol University.…”
Section: Methodsmentioning
confidence: 99%
“…For this study, the diagnosis of scrub typhus was confirmed by either 1) nested polymerase chain reaction (PCR) detection of the 16S ribosomal RNA gene or 56-kD protein gene 8,9 ; or 2) IFA detection of an IgM O. tsutsugamushi titer 1:400 or a 4-fold increase in IFA IgM titer, or an IgG titer 1:800 or a 4-fold increase in IFA IgG titer. 7,8 Non-scrub typhus patient samples. Serum samples (n = 62) from patients with laboratory-confirmed diagnosis of other tropical febrile illness were collected at the same study hospitals.…”
Section: Methodsmentioning
confidence: 99%
“…6 Subsequent clinical trials from Thailand support the use of ceftriaxone, cefotaxime, and azithromycin as well in this zoonotic infection. [7][8][9] Intravenous third generation cephalosporins have become the preferred agents for severe leptospirosis based on their proven efficacy, ease of use, availability, and ability to cover other etiologies of acute febrile illness when the diagnosis is in doubt. The potential efficacy of other cephalosporins in leptospirosis is less clear.…”
Section: Introductionmentioning
confidence: 99%